Clinical efficacy of transforaminal endoscopic lumbar discectomy for lumbar degenerative diseases: A minimum 6-year follow-up - Tang, Jin; Li, Ying; Wu, Congjun; Xie, Wei; Li, Xugui; Gan, Xuewen; Lu, Qilin (Frontiers in Surgery, 2022)
Background: TELD is widely applied for LDDs and satisfactory short-term outcomes have been achieved. However, the mid-term and long-term follow-up of this technique is still lacking. Objective: To retrospectively analyze the mid-term clinical efficacy of TELD for single-level LDDs and its effect on intervertebral disc degeneration with a minimum of 6-year follow-up. Methods: 64 patients with single-level LDDs who underwent TELD under local anesthesia in our department from December 2014 to December 2015 were observed. VAS, JOA and ODI were compared before operation, 3 months ，1 year after operation and at the last follow-up. DH, ROM and disc degeneration on standard lumbar lateral radiographs before operation and at the last follow-up were determined. Recurrence rate and operation-related complications during follow-up were recorded. Results: 64 cases were followed up for 6.4±0.1 years. There were no complications such as infection, epidural hematoma and nerve root injury. 1 patient (1.67%) was found to have dural rupture and cauda equina hernia during the operation. There were significant differences in VAS, JOA, ODI between preoperative and postoperative 3 months, 6 months, 1 year and last follow-up (P < 0 01), VAS, JOA, ODI at 3 months after operation were different from 6 months after operation (P < 0 05), and there were significant differences compared with preoperative, 1 year after operation and last follow up (P < 0 01). VAS, JOA and ODI at 6 months after operation were significantly different from those before operation (P < 0.01), but not significantly different from those at 1 year after operation and the last follow-up (P > 0.05). There was no significant difference in DH, ROM and the Pfirrmann grade of intervertebral disc preoperative and the last follow-up. During the follow-up period, 3 patients (4.69%) were recurrent, 13 patients (20.31%) had various degrees of POD, and 3 patients (4.69%) had various degrees of muscle weakness. Conclusion: TELD has a satisfactory mid-term efficacy, and has no significant effect on the DH, the stability of the intervertebral disc space, or on intervertebral disc degeneration. However, as expected, TELD was associated with some complications including recurrent disc herniation and POD.